Georgia : From Reformer to Performer - World Bank Group (World Bank, Washington, DC, 2018)
The fate of future generations of Georgians will be decided to start now. A girl born in Georgia today can expect to live for more than 86 years, to 2104. This girl, and her peers, will shape Georgia in the 21st century, but her future will also depend on the path that the country chooses today. What will her life look like when she becomes an adult? What will it take for her to be able to realize her dreams in Georgia, rather than abroad? What job prospects will the country offer? How can Georgia become a leading emerging-market economy and middle-class society, in which her children will have even greater opportunities? This Systematic Country Diagnostic (SCD) highlights the country’s core development challenges and opportunities. It takes stock of Georgia’s development progress since its ‘rebirth’ a quarter of a century ago. It also takes a forward look at the social and economic landscape, and possible futures that this Georgian girl and her peers will need to navigate. The SCD focuses on the twin goals of ending extreme poverty, which Georgia can achieve in the next decade, and boosting the incomes of households, specifically for those at the bottom of the income distribution, to create shared prosperity. The SCD also lays out the elements of a strategic vision to overcome obstacles and leverage opportunities in sustaining high growth, improving equity, and creating a sustainable future.